An evolutionary programming approach to optimize synchronous generator input power using area-based transient stability indexes - Hashim H.; Abidin I.Z.; Musirin I.; Siah Yap K.; Omar Y.R.; Zulkepali M.R. (Asian Research Publishing Network (ARPN), 2023)
Stable operation of a power system requires a continuous match between energy input to the prime movers and the electrical load of the system. Any change of load demand must be accompanied by a corresponding change in terms of the amount of energy prime mover given to the turbine system. When a power system is subjected to significant transient disturbances, the machine may lose synchronism to the system. If this were to happen, the machine's rotor angle will undergo wide variations, voltage and frequency may deviate widely from normal values. This paper presents the applications of Area-Based Transient Stability Indexes (TSI): COI Angle and COI Speed as a new technique to evaluate the impact of disturbances to power system stability and to optimize the mechanical input power of synchronous generators in order to prevent transient instability in a power system using Evolutionary Programming (EP) approach. Transient analysis is carried out using PSSE software on IEEE 118 Bus Test System at system conditions with various types of loads, static and dynamic. The optimization of the input power to generator is carried out using transient stability indexes as fitness functions for a three area IEEE 30 Bus and IEEE 118 Bus Test Systems respectively. Results obtained from the experiment revealed that the EP approach is able to give an optimal solution. 2005 - 2013 JATIT & LLS. All rights reserved.